GREEN ANALYTICAL TECHNIQUES FOR THE ESTIMATION OF RALTEGRAVIR IN DRUG AND PHARMACEUTICALS - SUMITHRA M; ARCHANA K (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to develop and validate a green solvent-assisted chromatographic method for the detection of raltegravir in bulk and pharmaceutical formulations. The study aimed to ensure an environmentally sustainable approach while maintaining precision, accuracy, and regulatory compliance. Methods: A chromatographic method was developed using ethanol and aqueous amine buffer (85:15%v/v) as the mobile phase at pH 4.0. The method was optimized with a flow rate of 1.0 mL/min, and the compound was detected at 247 nm. Validation was conducted following the International Council for Harmonization (ICH) guidelines, assessing key parameters such as linearity, limit of detection (LOD), limit of quantification (LOQ), and forced degradation studies. The greenness of the method was evaluated using various green chemistry assessment tools, including the Analytical GREEnness Approach (AGREE), green analytical procedure index (GAPI), Complex GAPI, red analytical performance index, blue applicability grade index, and Red Green Blue (RGB) assessment models. Results: The developed method achieved a retention time of 5.46 min and exhibited a strong linear relationship with a correlation coefficient (r²) of 0.999 within the concentration range of 3.0–15 μg/mL. The LOD and LOQ values were within acceptable criteria, demonstrating the method’s sensitivity. The greenness assessment revealed that the AGREE score was close to 1, while hexagonal charts with green centers confirmed the eco-friendliness of the method in comparison to reported conventional techniques. Forced degradation studies indicated acceptable degradation levels ranging from 5% to 20%, in compliance with ICH Q1B guidelines, ensuring the method’s robustness and stability-indicating capability. Conclusion: The proposed green solvent-assisted chromatographic method provides an eco-friendly, precise, and accurate approach for the analysis of raltegravir in bulk and pharmaceutical formulations. The method aligns with green analytical chemistry principles and regulatory guidelines, offering a sustainable alternative to conventional chromatographic techniques.